Beyond autism and technology: lessons from neurodiverse populations. Issue 2 (19th June 2017) - Brosnan, Mark; Holt, Samantha; Yuill, Nicola; Good, Judith; Parsons, Sarah
Abstract : Purpose: The purpose of this paper is to report on the sixth seminar in a seven-seminar series entitled, Innovative Technologies for Autism: Critical Reflections on Digital Bubbles, funded by the UK Economic and Social Research Council. The aim of this particular seminar was to reflect upon the implications from neurodiverse communities for the development of technology for autism. Design/methodology/approach: Presentations from key researchers and parental perspectives are reviewed, highlighting contemporary issues in neurodiverse populations that have important implications for autism. Findings: Whilst there are many conditions associated with autism, most commonly intellectual disability (learning difficulties), this is not reflected in research. In addition, for child-based research, researchers are at least a generation older than participants and have had different digital-childhoods. Involving neurodiverse populations within participatory design sessions can address both of these issues. Understanding the context of the issues that the participatory design sessions address is crucial for developing participatory design principles that extend from one condition to another. This includes understanding when findings based upon verbal populations can be extended to non-verbal populations. Originality/value: This paper offers up-to-date insights into how design principles from one condition extend to different conditions. Universal interaction and neurodiversity HCI are considered. This is important within neurodiverse populations, especially given the high rates of additional conditions that are associated with autism. Whilst the majority of autism research has involved verbal populations, the benefits of technology can extend to non-verbal populations.